The performance of the physical education professional in public health in Santa Catarina - Sierpinski, Tatiane Cristine; Rosa, Ricardo Clemente; Morales, Pedro Jorge Cortes; Salin, Mauren da Silva (Seven Editora, 2023)
This study aimed to analyze the performance of the Physical Education Professional (PEF) and identify which actions they develop in public health in Santa Catarina, as well as what are the difficulties and facilities of the performance. The present research is characterized as a mixed (QUAL>QUAN) and exploratory research model. Participated in the research 35 PEF that work in public health in the State of Santa Catarina. The research instrument used was a questionnaire developed by the researchers and made available via Google Forms®. This instrument is composed of 9 questions, of which 2 are open and 7 are mixed, forming two broad categories of analysis: "aspects of professional performance" (questions 1 to 6) and "training" (questions 7 to 9). The collected data were analyzed through descriptive statistics, organized in a Microsoft Excel® for Windows® spreadsheet. The statistical treatment was performed through the MAXQDA® software, version 2022, for qualitative data analysis. The results show that there is a predominance of performance in exercise programs with the population (FA-33/FR-94.28%), with the main difficulty being the lack of adequate environment for practice (FA-27/FR77.14%) and the main ease the respect and interaction between the professionals of the multidisciplinary team (FA-26/FR 74.28%), it was also possible to verify the understanding of the role of the PEF,  characterized by health promotion based on prevention with the practice of physical activity (Figure 3). The findings also show that the professionals consider their incipient training for the work (FA-27/FR-77.14%), as well as presenting the undergraduate disciplines that most contributed to the performance in the context of public health (figure 4). It is concluded that the PEF inserted in public health in Santa Catarina work by developing physical exercise programs in health prevention, being able to identify their facilities, being mainly the respect and rapport between the professionals of the team, and also the difficulties, characterized by the lack of adequate environments for the performance. DOI:https://doi.org/10.56238/globalhealthprespesc-049